1992
DOI: 10.1159/000243820
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Intake in Preterm Babies and Variation of Tubular Reabsorption for Phosphate per Liter Glomerular Filtrate

Abstract: Inadequate low intake of phosphorus can induce a hypophosphatemic depletion syndrome resulting in hypercalcemia, hypercalciuria, hypophosphatemia, and rickets. Tubular reabsorption for phosphate per liter glomerular filtration rate (TP/GFR) has been proposed as a reliable index of renal phosphate handling for all age groups. In the present study, carried out in 12 healthy premature babies fed unmodified pooled human milk and then a preterm formula for two periods of 10 days, we demonstrated clearly that TP/GFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…Several studies reported on Tp/GFR in more mature infants. In infants at 30-35 weeks GA, a median Tp/GFR value of 2.06 mmol/l was reported [7]. All of the values reported correspond well to the values we found in the group of 26-31 weeks GA. Several mechanisms could be responsible for the low Tp/GFR values in the infants 23-25 weeks GA. First, the extremely premature kidney could reabsorb phosphate poorly, even in the absence of kidney damage or phosphaturic medication.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies reported on Tp/GFR in more mature infants. In infants at 30-35 weeks GA, a median Tp/GFR value of 2.06 mmol/l was reported [7]. All of the values reported correspond well to the values we found in the group of 26-31 weeks GA. Several mechanisms could be responsible for the low Tp/GFR values in the infants 23-25 weeks GA. First, the extremely premature kidney could reabsorb phosphate poorly, even in the absence of kidney damage or phosphaturic medication.…”
Section: Discussionsupporting
confidence: 88%
“…These mechanisms could still be immature and contribute to higher Ox/Cr ratios in preterm infants. The higher Ca excretion in preterm infants could be secondary to lower urinary phosphate reabsorption leading to phosphate depletion despite higher dietary phosphate [3,8,10].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that calcium soft tissue retention is negligible, renal calcium load is highly dependent on the bone calcium deposition associated with phosphorus in the form of hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ) containing a molar Ca:P ratio of 1.67 (2.15 wt/wt). Thus, the main determinant of calcium urinary loss in preterm and term neonates is a relative phosphorus depletion [21,22]. This has been illustrated in balance studies performed in growing preterm infants fed human milk.…”
Section: Hypercalciuria In Preterm Infants Fed Human Milkmentioning
confidence: 98%